The Oslobreen Series, Upper Hecla Hoek of Ny Friesland, Spitsbergen - Gobbett, D. J.; Wilson, C. B. (Geological Magazine, 1960)
Abstract Six formations, totalling 1,210 metres and grouped as the Oslobreen Series, are dominantly of dolomite and limestone often with evidence of discontinuous deposition. They contain a Lower Cambrian and a Canadian fauna. The succession is similar to those of this age in N.W. Scotland, where a revised thickness is given, and in E. Greenland. A new species of Canadian trilobite ( Hystricurus ) is described in the Appendix.